College library model supporting students' psychological well-being and mental health - Perdaning Widyanti; Harini Desi Utami; Erna Mustika Indriani; Sukarjono Sukarjono (Perpustakaan Universitas Gadjah Mada, 2025)
Introduction. Students’ mental health is vital in higher education. Libraries serve as information hubs and spaces for relaxation, stress relief, and psychological support. This study explores library usage, key services and facilities for well-being, and the library’s role as a common space. Research Methods. An exploratory sequential design is applied. The qualitative phase involves interviews and observations at UGM and UMY libraries to identify key indicators of services and facilities. These results inform the quantitative phase, using questionnaires distributed to 60 student users. Data Analysis. Qualitative data are analyzed through reduction, presentation, and conclusion drawing. Quantitative data are analyzed using descriptive statistics and simple linear regression. Results. Qualitative findings highlight the importance of consultation services, academic support, flexible spaces, and relaxation areas for student well-being. Quantitative analysis confirms significant effects of library services (t = 5.600; p < 0.001) and facilities (t = 5.300; p < 0.001), with a combined influence F = 29.732 (p < 0.001) and R² = 0.672. Conclusion. Modern libraries should combine learning and relaxation functions. Strengthening design, technology, and psychosocial services through evaluation and collaboration is essential to create inclusive spaces that foster student mental health.